The competition economics of financial fair play - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2014)
This paper provides an economic analysis of the competition effects of UEFA's financial fair play regulations. It concludes that the restrictive effects of the break-even rule cannot be justified by a legitimate objective defense (according to European competition policy) because significant financial problems due to overinvestment are not inherent to European football.
Keywords: 330; financial fair play; sports economics; competition economics; European competition policy; football; soccer; overinvestment; rat race